Antimicrobial effect of Trigonella foenum graecum Seed Extracts against Tested Bacteria Isolated from Meat and Fish - Suad K. Ibrahim; Samira M. Yaseen; Raghad H. Nasser (Journal of Madenat Alelem University College, 2015)
A qualitative chemical test was performed on functional groups extracted from fenugreek plant and its extracts (aqueous, alcoholic and volatile oil). Results revealed that fenugreek seeds contain the main functional groups, while extracts are varied accorodihg to their content of functional groups qualitatively and quantitively. Moreover, inhibition activity was tested for extracts of fenugreek seeds (aqueous, alcoholic and volatile oil). against gram negative (Salmonella typhimurium, Escherichia coli and Pseudomonas aeruginosa) and gram positive (Staphylococcus aureus) by the ager well diffusion method. Data have revealed that inhibition activity was different in accoradance with extract solvent and the tested microorgan. Oil extract (15)% give the most signficant difference comparing with other extracts in inhibition tested bacteria, whereby radial of inhibition zones were (24, 26.66, 28.22, 25 , 30 ) mm in E. coli, S. aureus, S. typhimurium, P. aeuginosa respectively, ethanol(alcohlic extract) (15)% was the second efficient extract while cold aqueous extract 25% gave the minimum inhibition activity. S. typhimurium showed the highest resistance towards cold aqeuous extract (25)% compared with other bacterial test. Further more, oiled extracts (1-5)% were tested against bacterial isolates. (1, 2, 3)% showed good inhibition activity. Oiled extract activity ( from 0.5% to 2% )was tested in reduction the total number of bacteria in meat and fish, activity was varied during (2, 4, 6, 8, 10) day, after treatment of meat and fish with oiled extract at (2)°C comparing with other sample not treated by oiled extract (positive control). Result suggested that oiled extract 2% ability was the best in reduction of bacterial cells and correspondent with the central device for standardization and quantitiative control of meat safe for human consumption. Inhibition activity MIC and MBC was applied against bacterial tests above. The minimum inhibitor concentration (MIC) and the minimum killer concentration (MBC) for oiled extract of fenugreek seeds in tested bacterial was 0.5%.